2019
DOI: 10.3390/geriatrics4020036
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of Polypharmacy in Elderly Patients in Saudi Arabia

Abstract: Background/Objectives: Saudi Arabia has a great percentage of geriatric patients associated with multiple chronic diseases who require close attention and monitoring for their medications. The purpose of this study is to develop a full-framed picture about the utilization of medications for geriatric patients and how to provide better health-care management. Methodology: A retrospective cross-sectional study targeting patients 65 years of age and older, who are taking multiple chronic medications for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 23 publications
3
26
1
1
Order By: Relevance
“…The prevalence of polypharmacy in the present study is dramatically higher than that identified in other regional and international studies. A recent study conducted in Saudi Arabia among a sample of 3009 older adults found that 55% of them were exposed to polypharmacy [30]. Also, a study in Kuwait showed that more than 60% of the older adults had polypharmacy [31].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of polypharmacy in the present study is dramatically higher than that identified in other regional and international studies. A recent study conducted in Saudi Arabia among a sample of 3009 older adults found that 55% of them were exposed to polypharmacy [30]. Also, a study in Kuwait showed that more than 60% of the older adults had polypharmacy [31].…”
Section: Discussionmentioning
confidence: 99%
“…This older population survey showed high prevalence of hypertension (28.5%) and diabetes mellitus (28.7%) among the older Saudi population. A retrospective crosssectional study 21 targeting 3009 older Saudi patient profiles revealed that 55% were suffering from polypharmacy, with an average of 6.4 medications prescribed for patients aged 65-70 years, and an average of 4.2 medications prescribed for those aged ≥71 years.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The Middle East respiratory syndrome (MERS-CoV), severe acute respiratory syndrome (SARS-CoV), SARSrelated coronavirus-2 (SARS- , and coronavirus disease ( are members of the same family as coronavirus. 50 These viruses may lead to fatal outcomes in humans, including acute respiratory distress syndrome, multiorgan failure, and death, particularly in geriatrics patients with multiple morbidities. 4, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]49,53 Various studies reported that COVID-19 has a similar pathogenic potential to cause respiratory complications, disability, and death as SARS-CoV and MERS-CoV.…”
Section: Polypharmacy and Potentially Inappropriate Prescribingmentioning
confidence: 99%